We are given the expression of the equation of a circle that is x2 + y2 + 14x + 2y + 14 = 0. Using ocmpleting the squares:
x2 + y2 + 14x + 2y + 14 = 0(x+7)^2 + (y+1) ^2 = -14 + 49 + 1(x+7)^2 + (y+1) ^2 = 36 center thus is at (-7,-1) and the radius is equal ot square root of 36 equal to 6.
The first statement is true, because the two negative signs cancel each other out. However, the second is false because any time you multiply a positive number by a negative number the product is always negative. Therefore 4x-6=-24
I think you go to where x=-1 and the y is the answer